The Effect of Job Satisfaction on Organizational Commitments and Organizational Citizenship Behavior - Jro Mangku Deny Saputra; I Gede Riana (Journal of Multidisciplinary Academic, 2021)
Human resources have an important role due to organizational effectiveness and success rate with highly dependent on the quality and performance of human resources. In this study aims to analyse the effect of job satisfaction on organizational commitment and organizational citizenship behaviour. This research was conducted in a mobile shop with 40 respondents. Here, the data was collected by distributing questionnaires to respondents using a list of statements related to the variables used. The collected data were analysed using Warp PLS software. The results showed that job satisfaction has a positive and significant effect on organizational commitment and organizational citizenship behaviour with value of highest coefficient path around 0.307 from testing result. This study also indicated that job satisfaction did not have a significant effect on organizational citizenship behaviour. The research implication informs that increasing organizational citizenship behaviour can be done by creating job satisfaction for employees through appropriate rewards and providing guarantees for employees to get justice in the workplace. Finally, the job satisfaction effect has been studied also applied as a mechanism to assess workplace over Gianyar, Bali, Indonesia in near future.